Phase-Locked Loop Based Second Order Generalized Integrator for Electric Vehicle Single-Phase Charger. (May 2017) - Pan, Liwen; Zhang, Chengning
Abstract: The phase-locked loop (PLL) is a crucial part in the control of an electric vehicle single-phase charger. A variety of PLL technologies have been proposed in literature. Among these, the second order generalized integrator (SOGI) methods have satisfactory steady-state and dynamic performance, however, its application is limited to three-phase converter. This paper exploits the application of SOGI method in single-phase converter. The paper describes the modifications of the SOGI structure and the influence of parameters on the system performance. The proposed control strategy added a band-stop filter to filter 2 nd ripple frequency and a trapezoidal discretization method. The simulation results based on MATLAB/Simulink are provided to verify the effectiveness of the suggested approach.